SOCIAL REPRESENTATIONS OF SCIENCE TEACHING IN EARLY CHILDHOOD EDUCATION - Gonzalez, Amanda Dourado; Gomes, Luciano Carvalhais (Seven Editora, 2025)
This study aims to investigate the social representations of early childhood education teachers regarding science teaching. The research seeks to understand how these social actors perceive the importance, challenges, and practices related to science teaching at this educational stage. Through qualitative field research based on focus groups, the study contributes to the understanding of the factors that influence perceptions and practices related to science teaching, in order to provide support for working relationships in this area of early childhood education. The results, discussions, and initial considerations identify the need for studies focused on social representations among teachers in early childhood education focused on science teaching. DOI: https://doi.org/10.56238/sevened2025.030-023